Vasculitis and vasculopathy associated with inborn errors of immunity: an overview - Federici, Silvia; Cinicola, Bianca Laura; La Torre, Francesco; Castagnoli, Riccardo; Lougaris, Vassilios; Giardino, Giuliana; Volpi, Stefano; Caorsi, Roberta; Leonardi, Lucia; Corrente, Stefania; Soresina, Annarosa; Cancrini, Caterina; et al. (Frontiers in Pediatrics, 2024)
Systemic autoinflammatory diseases (SAIDs) are disorders of the innate immunity, characterized by apparently unprovoked recurrent flares of systemic inflammation usually characterized by fever associated to clinical manifestation involving mainly the musculoskeletal, mucocutaneous, gastrointestinal and nervous systems. Several conditions present a various, sometimes prominent, involvement of the vascular system too with features of vasculitis characterized by variable target vessel involvement and organ damage. Here we report a systematic review of vasculitis and vasculopathies associated with inborn errors of immunity.